Corrosion Behavior in Different Media of Dissimilar Super Duplex Stainless Steel 2507 and Austenitic Stainless Steel 316 Welding by Using GTAW Process with Filler Type 316L - Abdulrahman H. Abbood; Mohammed Helan Sir; Nasri S. M. Namer (Journal of Techniques)
The Super duplex stainless steel is the best of the stainless steel types because duplex stainless steel contains two phases, ferritic and austenitic, which promote this alloy's mechanical and corrosion properties compared to other types. This study will investigate the corrosion behaviour of weld metal and base metals in acidic and salty media. At 20 C, hydrochloric acid (1M, 3M, and 5M) was studied beside sodium chloride NaCl (1 wt%, 3.5 wt%, and 5 wt%). The potentiostat test results show that the effect of HCl is more aggressive than NaCl in all cases, as HCl is a strong acid. The results showed the 316 base metal being the weakest area compared with others (2507 BM and W.M.). The microstructure has been checked before and after the corrosion test and pitting corrosion has been found in the 316 base metal only, while the weld metal and 2507 base metal surfaces were free of pitting influence. Due to the welding technique and using a cooper back strip, the microstructure shows minor grain growth in the heat-affected zones (HAZ) on both weld sides. The micro-hardness test revealed that the duplex stainless steel had a higher value than the weld metal and the 316-base metal. The weld metal had a minor increase over the base metal because of the migration of the elements like chromium and nickel.